Visuospatial short-term and working memory disturbance in the primary progressive aphasias: Neuroanatomical and clinical implications. (November 2020) - Foxe, David; Irish, Muireann; Roquet, Daniel; Scharfenberg, Angela; Bradshaw, Nathan; Hodges, John R.; Burrell, James R.; Piguet, Olivier
Abstract: Introduction: Primary progressive aphasia (PPA) comprises three main variants: logopenic (lv-PPA), non-fluent (nfv-PPA) and semantic variant (sv-PPA). Differentiating the language profiles of the PPA variants remains challenging, especially for lv-PPA and nfv-PPA. As such, diagnostic tools that do not rely on speech and language may offer some utility. Here, we investigated the short-term and working memory profiles of the PPA variants and typical Alzheimer's disease (AD), with a particular interest in the visuospatial system. We hypothesised visuospatial short-term and working memory would be more compromised in lv-PPA and AD than in the other PPA variants, and that this would relate to degeneration of posterior temporoparietal brain regions. Method: Thirty-three lv-PPA, 26 nfv-PPA, 31 sv-PPA and 58 AD patients, and 45 matched healthy controls were recruited. All participants completed the WMS-III Spatial and Digit Span tasks and underwent a structural brain MRI for voxel-based morphometry analyses. Results: Relative to Controls, Spatial Span Forward (SSF) performance was impaired in lv-PPA and AD but not in nfv-PPA or sv-PPA. In contrast, Digit Span Forward (DSF) performance was impaired in lv-PPA and nfv-PPA (to a similar level), and AD, but was relatively intact in sv-PPA. As expected, most backward span scores across both modalities were lower than forward span scores. Neuroimaging analyses revealed that SSF and SSB performance in all patients combined correlated with grey matter intensity decrease in several clusters located in temporo-parieto-occipital brain regions. Post-hoc group comparisons of these regions showed that grey matter loss was more extensive in the lv-PPA and AD groups than in the nfv-PPA and sv-PPA groups. Conclusions: The findings suggest that the visuospatial short-term and working memory profiles of the PPA variants are separable and likely reflect their distinct patterns of temporo-parieto-occipital brain atrophy.